Kajian Tafsir Maudhu’i: Toleransi Antarumat Beragama dalam Perspektif Al-Qur'an - Muhammad Jaatsiy Abdillah (Yayasan Darusssalam Bengkulu, 2025)
Tolerance among Religious Communities from the Perspective of the Qur’an is one of the fundamental principles of Islam, emphasizing the importance of respecting differences in belief without any form of coercion. This article aims to examine the meaning of tolerance, the concept of tolerance, and the interpretation of key verses such as Surah Al-Baqarah [2:256] and Surah Al-Kafirun [109:6] as theological foundations for fostering harmonious interfaith relations. Using a qualitative method through library research, the discussion focuses on the core principles of tolerance in Islam, including freedom of religion, social justice, and appreciation of pluralism. Moreover, the article analyzes the challenges in implementing the values of tolerance in society, such as fanaticism, radicalism, and narrow, exclusive interpretations of religion. The findings reveal that Islam views tolerance as a form of respect for human dignity and as a foundation for building a peaceful and harmonious society. Therefore, this article provides a comprehensive understanding of the teachings of tolerance in the Qur’an and their relevance in multicultural and pluralistic societies such as Indonesia.